Efficacy and tolerability of trifluridine/tipiracil in patients with refractory metastatic colorectal cancer at the general hospital of Šibenik-Knin country - Lana Jajac-Bručić; Filip Grubišić-Čabo; Josipa Jović-Zlatović; Ivan Krečak (Libri Oncologici, 2021)
In randomized clinical trials, trifluridine / tipiracil (TT) demonstrated beneficial effects on progression-free survival (PFS) and overall survival (OS) in patients with refractory metastatic colorectal cancer (mCRC). The aim of this unicentric study was to evaluate the efficacy and safety of TT in patients with refractory mCRC in everyday clinical practice. Treatment outcomes of 20 patients were retrospectively analyzed. The median OS was 6.25 months (range 1-18) and the median PFS was 3 months (range 2–13). The most common (80%) side effect of TT was neutropenia and 35% of patients had neutropeniagrades 3 of 4; however, only two patients (10%) had neutropenic fever and no deaths wereattributable to neutropenia. In conclusion, treatment outcomes in this real-life study seem comparable to those from randomized clinical trials.